Interplay of Forces and the Immune Response for Functional Tendon Regeneration - Yang, Yuwei; Wu, Yicong; Zhou, Ke; Wu, Dongmei; Yao, Xudong; Heng, Boon Chin; Zhou, Jing; Liu, Hua; Ouyang, Hongwei (Frontiers in Cell and Developmental Biology, 2021)
Tendon injury commonly occur during sports activity, which may cause interruption or rapid decline in athletic career. Tensile strength, as one aspect of tendon biomechanical properties, is the main parameter of tendon function. Tendon injury will induce an immune response and cause the loss of tensile strength. Regulation of mechanical forces during tendon healing also changes immune response to improve regeneration. Here, the effects of internal/external forces and immune response on tendon regeneration are reviewed. The interaction between immune response and internal/external forces during tendon regeneration is critically examined and compared, in relation to other tissues. In conclusion, it is essential to maintain a fine balance between internal/external forces and immune response, to optimize tendon functional regeneration.